Enforcement of justice in minor crimes for the establishment of law and order in Indonesia - Wahyudi, Wahyudi; Wibowo, Basuki Rekso; Widjaja, Gunawan; Sirait, Timbo Mangaranap (International research journal of management, IT and social sciences, 2025)
Since crime was known in society, criminal law experts from ancient times initially considered punishment as a means of treatment (remedy) to cure perpetrators of criminal acts by giving sanctions that have a deterrent effect, so that criminals no longer repeat their actions, including for minor criminal cases. The research was conducted using the Normative Juridical research method with literature studies, with the formulation of the problem to be raised, namely (1) How is the Law Enforcement of Minor Criminal Offenses Based on Restorative Justice in Order to Create Order in the Criminal Law and Sentencing System, and a Comparison of the Legal Basis in Indonesia with the United States and Singapore? and (2) What is the Ideal Concept of Law Enforcement of Minor Criminal Offenses Based on Restorative Justice Based on Progressive Legal Theory that is Expected in the Future (Ius Constituendum)?, and it is concluded, Firstly that the enforcement of minor criminal law with Restorative Justice in order to create order in the Criminal Law and Punishment System in Indonesia still has dualism in its law enforcement by law enforcers,